2017
DOI: 10.1007/s00414-017-1551-4
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of touch DNA on burglary-related tools

Abstract: Experts are increasingly concerned by issues regarding the activity level of DNA stains. A case from our burglary-related casework pointed out the need for experiments regarding the persistence of DNA when more than one person touched a tool handle. We performed short tandem repeat (STR) analyses for three groups of tools: (1) personal and mock owned tools; (2) tools, which were first "owned" by a first user and then handled in a burglary action by a second user; and (3) tools, which were first owned by a firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 49 publications
1
32
2
Order By: Relevance
“…Whilst duration, frequency and manner of contact (including contact points and levels of pressure and friction) will have impacted the profiles observed [21,26,27], it is likely that the shedder status [17,[28][29][30][31][32] of the office owners and temporary occupants will also have impacted the profiles generated. For example, while the shedder status of the participants in this study is unknown, the temporary occupants of O1 and O4 in Lab A, and O1 in Lab B, were rarely present on the tested items within the offices they occupied, whereas the office owners were the sole or major/majority contributor to profiles from most items (thus the office owner may be a good shedder and/or the temporary occupier a poor shedder).…”
Section: Discussionmentioning
confidence: 99%
“…Whilst duration, frequency and manner of contact (including contact points and levels of pressure and friction) will have impacted the profiles observed [21,26,27], it is likely that the shedder status [17,[28][29][30][31][32] of the office owners and temporary occupants will also have impacted the profiles generated. For example, while the shedder status of the participants in this study is unknown, the temporary occupants of O1 and O4 in Lab A, and O1 in Lab B, were rarely present on the tested items within the offices they occupied, whereas the office owners were the sole or major/majority contributor to profiles from most items (thus the office owner may be a good shedder and/or the temporary occupier a poor shedder).…”
Section: Discussionmentioning
confidence: 99%
“…However, in other studies where the circumstances were less controlled and/or optimised, the non-self component of the transferred profile was the major or only contributor in no more than 3% of samples [63,75,123,139,142,143].…”
Section: Accepted Manuscriptmentioning
confidence: 89%
“…Furthermore, the level of interaction (from a single static contact of a specific sub-area of an object, to multiple, frequent, varied manners and locations of contact) of a handled object with another object will also vary widely. A study by Pfeifer and Wiegand [123] demonstrated the impact of different intensities of handling a tool (intense mock break-in to a premises versus normal use of a tool according to its designed purpose) on the types of profiles subsequently collected.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations